2015
DOI: 10.1096/fj.14-266023
|View full text |Cite
|
Sign up to set email alerts
|

Armet is an effector protein mediating aphid‐plant interactions

Abstract: Aphid saliva is predicted to contain proteins that modulate plant defenses and facilitate feeding. Armet is a well-characterized bifunctional protein in mammalian systems. Here we report a new role of Armet, namely as an effector protein in the pea aphid, Acyrthosiphon pisum. Pea aphid Armet's physical and chemical properties and its intracellular role are comparable to those reported for mammalian Armets. Uniquely, we detected Armet in aphid watery saliva and in the phloem sap of fava beans fed on by aphids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 43 publications
0
89
1
Order By: Relevance
“…As a result, there is no capacity to increase plant susceptibility to the aphid by disrupting Ca 2+ signaling. The suppression of Arabidopsis defense by aphids is achieved via effector proteins (Bos et al, 2010;Hogenhout and Bos, 2011;Pitino and Hogenhout, 2013;Atamian et al, 2013;Elzinga et al, 2014;Naessens et al, 2015;Wang et al, 2015;Kettles and Kaloshian, 2016) that are injected into epidermal and mesophyll cells during feeding (Martín et al, 1997;Moreno et al, 2011;Mugford et al, 2016). These effectors may actively suppress the feeding site [Ca 2+ ] cyt elevations, as aphid saliva contains Ca 2+ binding proteins Carolan et al, 2009;Rao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there is no capacity to increase plant susceptibility to the aphid by disrupting Ca 2+ signaling. The suppression of Arabidopsis defense by aphids is achieved via effector proteins (Bos et al, 2010;Hogenhout and Bos, 2011;Pitino and Hogenhout, 2013;Atamian et al, 2013;Elzinga et al, 2014;Naessens et al, 2015;Wang et al, 2015;Kettles and Kaloshian, 2016) that are injected into epidermal and mesophyll cells during feeding (Martín et al, 1997;Moreno et al, 2011;Mugford et al, 2016). These effectors may actively suppress the feeding site [Ca 2+ ] cyt elevations, as aphid saliva contains Ca 2+ binding proteins Carolan et al, 2009;Rao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aphid saliva contains Ca 2+ binding proteins Carolan et al, 2009;Rao et al, 2013), and application of saliva to legume phloemplugging proteins results in their contraction . Aphid saliva also contains effector molecules that suppress plant defense (Bos et al, 2010;Pitino and Hogenhout, 2013;Atamian et al, 2013;Naessens et al, 2015;Wang et al, 2015;Kettles and Kaloshian, 2016), as observed with microbial pathogens (Jones and Dangl, 2006;Galán et al, 2014) and chewing insects (Musser et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…for salivary proteins-such as effectors-has been reported for aphids as well (108,110,129). Elzinga et al (129) suggested that the differential expression of salivary effector genes represents a strategy to avoid activation of defenses and to facilitate feeding.…”
Section: Identification Of Salivary Gland Proteinsmentioning
confidence: 99%
“…Expressing C002 from the green peach aphid Myzus persicae in Nicotiana benthamiana increased aphid reproduction on these plants, whereas reducing C002 expression in aphids by plant-mediated RNA interference (RNAi) reduced aphid fecundity (Bos et al, 2010;Pitino et al, 2011). Other salivary proteins, such as Glc oxidase from the corn earworm Helicoverpa zea (Musser et al, 2002), calcium-binding proteins from the vetch aphid Megoura viciae (Will et al, 2007), Mp10 and Mp55 from the green peach aphid (Bos et al, 2010;Elzinga et al, 2014), structural sheath proteins from the grain aphid Sitobion avenae (Abdellatef et al, 2015), Me10 and Me23 from the potato aphid Macrosiphum euphorbiae (Atamian et al, 2013), and Armet from the pea aphid (Wang et al, 2015), also have been found to increase herbivore performance. Thus, herbivore effectors play a central role in overcoming plant defenses and helping the herbivore establish a population on host plants.…”
mentioning
confidence: 99%